Dampak Ketidakstabilan Harga Kelapa Sawit Bagi Kesejahteraan Petani di Desa Nagori Bayu Bagasan Kecamatan Tanah Jawa Kabupaten Simalungun - Ardiansyah Sinaga; Randa Putra Kasea Sinaga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research was conducted to monitor and analyze the impact of unstable palm oil prices on the welfare of farmers in Nagori Bayu Bagasan Village, Tanah Jawa District, Simalungun Regency. As one of the pillars of the country's economy, the agricultural sector is expected to increase income, especially for residents who are still below the poverty line. The aim of this research is to find out the impact ofunstable palm oil prices on the welfare of palm oil farmers in Nagori Bayu Bagasanvillage, Tanah Jawa District, Simalungun Regency. The research method used in this research is descriptive qualitative research in which the researcher will describethe impact of oil palm price instability in Nagori Bayu Bagasan Village, Tanah Jawa District. The results of this research are that the community in Nagori Bayu BagasanVillage, Tanah Jawa District, if the price of palm oil experiences instability, it can cause low income for oil palm farmers and high expenditure for their basic living needs. Therefore, to achieve a prosperous standard of living for society cannot be separated from education, because the higher the level of education, the higher thequality of work that is obtained, the higher the income earned.